THE CLINICAL IMPORTANCE OF TOPOGRAPHIC ANATOMY IN SURGICAL PRACTICE: FOCUS ON NEUROVASCULAR BUNDLES - Suyunova Zamira Axatovna; Awaish Asim (TADQIQOTLAR, 2025)
Abstract Topographic anatomy plays a central role in operational surgery, particularly when dealing with neurovascular structures. Understanding the spatial relationships of arteries,  veins,  and  nerves  is  essential  for  preventing  intraoperative  injuries  and postoperative complications. This article explores the role of neurovascular bundles in surgical anatomy and their clinical significance for surgical interventions.